Who Wants a Cheap Rhinoceros? - Silverstein, Shel (New York, N.Y. : Simon & Schuster, 2002)
There are lots of things a rhinoceros can do around one's house, including eating bad report cards before one's parents see them, tiptoeing downstairs for a midnight snack, and collecting extra allowance.
"Revised and expanded edition of a book previously published under psuedonym, Uncle Shelby"--T.p. verso.
AD 320
Accelerated Reader
Keywords: Rhinoceroses -- Juvenile fiction